"I Swear I Will Never Betray You": Factors Reported by Spouses as Helping Them Resist Extramarital Sex in Relation to Gender, Marriage Length, and Religiosity. Issue 2 (12th February 2018) - Ziv, Ido; Lubin, Or Ben-Haim; Asher, Sapir
Abstract : Studies suggest that married people frequently engage in intimate relationships with people other than their spouses, and the literature has extensively examined motives for doing so. However, less is known about what factors prevent spouses from engaging in extramarital sex. While investment theory, interdependence theory, and moral theories offer insights into this question, they have not been subject to much empirical research. We examine these theories in relation to several characteristics of individuals and couples: gender, length of the marriage, and religiosity. In two studies, 423 participants completed a questionnaire on the perceived importance of 29 reasons to resist the temptation for extramarital sex. Participants also reported the likelihood that they would engage in extramarital sex if the opportunity presented itself. Results show that being female, more religious, and married for less time were associated with greater expectations of refraining from extramarital sex when presented with a hypothetical scenario. Multiple hierarchical regression showed that among factors relevant to conscious decision making, moral standards and fundamental anxieties (fear of remaining alone) predict expectations of refraining from extramarital sex better than concerns about effects on the children or the other participant.